The challenge of comparing digitally captured signatures registered with different software and hardware. (October 2021) - Zimmer, J.; Kalantzis, N.; Dziedzic, T.; Heckeroth, J.; Kupferschmid, E.; Fernandes, C.; Geistová Čakovská, B.; Branco, M.J.; Axelsson Spjuth, K.; Vaccarone, P.; Kerkhoff, A.
Highlights: Data of signatures digitally captured with different equipment may differ. Variations in data scaling when different equipment are used for signatures capturing. Data normalisation of digitally captured signatures following the ISO/IEC 19794–7. Normalisation of digitally captured signatures data requires scaling information. Abstract: Along with the growing popularity of electronic documents authorised with digitally captured signatures, such evidence has appeared in the work of forensic practitioners. Many different vendors offer signature pads with varying specifications. It is therefore expected that forensic handwriting experts will be called upon to compare questioned and known samples captured with completely or partially different hardware and software combinations. Such cases may be challenging as numerical handwriting data produced by various equipment may differ not only in the type of information captured and its quality, but also in its structure and coding. In this research, numerical data of handwriting – i.e. spatial coordinates, force, and time values – were acquired with 26 different combinations of hardware and software to study characteristics of their coding. The analysis of samples revealed that scaling of numerical data is not only hardware but also software dependent. Therefore, their compliance with the ISO/IEC 19794–7 standard is recommended to improve the data interoperability. This standard emphasizes the importance of supplementing numerical signature data with scaling ratios of the used signing solution. The paper also includes descriptions of several phenomena observed in the acquired data to highlight possible pitfalls in performing inter-solution comparisons in casework.